Valve Hemodynamics by Valve Size and 1-Year Survival Following Implantation of the Portico Valve in the Multicenter CONFIDENCE Registry - Möllmann, Helge; Linke, Axel; Nombela-Franco, Luis; Sluka, Martin; Francisco Oteo Dominguez, Juan; Montorfano, Matteo; Kim, Won Keun; Arnold, Martin; Vasa-Nicotera, Mariuca; Fichtlscherer, Stephan; Conradi, Lenard; Camuglia, Anthony; et al. (Structural Heart, 2023)
Background: The CONtrolled delivery For ImproveD outcomEs with cliNiCal Evidence registry was initiated to characterize the clinical safety and device performance from experienced transcatheter aortic valve implantation (TAVI) centers in Europe and Australia that use the Portico valve to treat patients with severe aortic stenosis. We herein report for the first time the valve performance at 30-day across all implanted valve sizes and the 1-year survival from this registry. Methods: This was a prospective, multicenter, single-arm observational clinical investigation of patients clinically indicated for implantation of a Portico valve in experienced TAVI centers. Patients were treated with a commercially available valve (size 23, 25, 27, or 29 mm) using either the first-generation delivery system (DS) (n = 501) or the second-generation (FlexNav) DS (n = 500). Adverse events were adjudicated by an independent clinical events committee according to Valve Academic Research Consortium-2 criteria. Echocardiographic outcomes were assessed at 30 days by an independent core laboratory, and a survival check was performed at 1 year. Results: We enrolled 1001 patients (82.0 years, 62.5% female, 63.7% New York Heart Association functional class III/IV at baseline) from 27 clinical sites in 8 countries across Europe and one site in Australia. Implantation of a single valve was successful in 97.5% of subjects. Valve hemodynamics at 30 days were substantially improved relative to baseline, with large aortic valve areas and low mean gradients across all implanted valve sizes (aortic valve areas were 1.7 ± 0.4, 1.7 ± 0.5, 1.8 ± 0.5, and 2.0 ± 0.5 cm2, and mean gradients were 7.0 ± 2.7, 7.5 ± 4.7, 7.3 ± 3.3, and 6.4 ± 3.3 mmHg for 23, 25, 27, and 29 mm valve sizes, respectively). Across all implanted valve sizes, most patients (77.1%) had no patient-prosthesis mismatch. Death from any cause within 1 year occurred in 13.7% of the patients in the first-generation DS group as compared with 11.0% in the second-generation DS group (p = 0.2). Conclusions: The Portico valve demonstrated excellent hemodynamic performance across all valve sizes in a large cohort of subjects implanted in experienced TAVI centers. One-year survival rates were favorable when using both the first-generation and second-generation (FlexNav) DSs in this high-risk cohort. ClinicalTrials.gov Identifier: NCT03752866.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Aortic stenosis; Self-expanding; TAVI; TAVR; Transcatheter aortic valve implantation; Transcatheter aortic valve replacement